Exogeneous Shocks, Resilience and the Evolution of Public Governance, the Case of Finland - Virtanen, Petri; Yli-Viikari, Tytti (Springer, 2021)
From a public policy perspective, resilience can be defined in a twofold manner. First, it refers to an adaptation mechanism associated with societal complexity. The nature, dynamics, and functions of this adaptation mechanism build upon government structures and the traditions of the given administrative–political system in the country in question. As far as the institutions and organizations in the public domain are concerned the components of resilience can be understood as properties, abilities, or capabilities. In practice, resilience as an adaptation mechanism requires strategic sensitivity, resource fluidity, and collective commitment among political decision-makers and government officials, particularly top civil servants. Second, resilience can be conceived of as a policy or organizational goal in...
Keywords: Resilience as a policy goal; Resilience as an adaptation mechanism; Risk management implementation in public institutions; Strategically agile government; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|